Educators’ Perceptions and Curriculum History in Somalia - Essa, Fawzia Osman (2021)
This study analysed the connection between educators’ perceptions and curriculum history of secondary schools in Somalia. With the utilisation of descriptive research design, a self administered questionnaire and an interview guide were employed to collect information which was used to achieve the specific objective of assessing the effect of educators’ perceptions on curriculum history of secondary schools in Somalia . The study adopted a mixed methods paradigm with descriptive research design , quantitative and qualitative approaches. A sample of 300 participants were chosen using Slovene’s formula. Data was collected using survey questionnaire and interview schedule and analyzed using descriptive statistics and chi-square test for quantitative data and thematic sythesis was used for analyzing qualitative data .The study findings established a significant relationship between educators’ perceptions and curriculum history of secondary schools in Somalia . The study concluded by proposing a model that can assist policy makers in Somalia to change current history curricula to construct one that supports a Somalia national identity . From the study findings, the researcher recommended that using a humanistic approach to curriculum evaluation in post conflict contexts may help teachers to explore people’s perceptions, attitudes, and beliefs. Keywords: Educators’ perceptions, Curriculum history, National identity, Somalia.